2009
DOI: 10.1136/hrt.2008.161091
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin treatment in patients with chronic heart failure: a meta-analysis

Abstract: In chronic HF, treatment with ESPs is not associated with a higher mortality rate or more adverse events, whereas a beneficial effect on HF hospitalisation is seen. These outcomes are in contrast with studies in cancer and kidney disease, and support a large phase III morbidity and mortality trial of anaemia correction in patients with chronic HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
70
3
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(75 citation statements)
references
References 31 publications
(41 reference statements)
0
70
3
2
Order By: Relevance
“…Several studies have focused on the effect of anemia correction, usually by iron and erythropoietin or darbopoietin, on exercise performance, measured either by peak _ VO 2 , exercise tolerance or by distance walked at the 6 min walking test, in both HF and non-HF patients [21][22][23][24][25][26][27][28][29]. However, only four [21][22][23] reports all based on small studies, showed the effect of anemia correction on peak exercise _ VO 2 in HF patients, with discordant findings.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have focused on the effect of anemia correction, usually by iron and erythropoietin or darbopoietin, on exercise performance, measured either by peak _ VO 2 , exercise tolerance or by distance walked at the 6 min walking test, in both HF and non-HF patients [21][22][23][24][25][26][27][28][29]. However, only four [21][22][23] reports all based on small studies, showed the effect of anemia correction on peak exercise _ VO 2 in HF patients, with discordant findings.…”
Section: Discussionmentioning
confidence: 97%
“…They found that patients treated with ESAs had a 47% reduction in HF related hospitalizations. They did not find a difference in mortality between the two groups, or any increase in risk of hypertension or venous thrombosis in the ESAs treated arms, 83 but the sample size may have still been too small. 83 Silverberg reported on an analysis of 10 RCTs.…”
Section: Dovepressmentioning
confidence: 94%
“…They did not find a difference in mortality between the two groups, or any increase in risk of hypertension or venous thrombosis in the ESAs treated arms, 83 but the sample size may have still been too small. 83 Silverberg reported on an analysis of 10 RCTs. These studies succeeded in raising mean hemoglobin to 12 to 13 g/dL, with no adverse effects and some benefits.…”
Section: Dovepressmentioning
confidence: 94%
“…In a recent meta-analysis of seven of these randomized trials of erythropoietic agents in CHF patients, including 363 treated patients and 287 controls, there was a significantly lower risk for CHF hospitalization (RR, 0.59; p ϭ .006) [69]. No differences occurred in mortality or in the incidence of hypertension, venous thrombosis, pulmonary embolus, cerebrovascular disorder, myocardial infarction, or other cardiovascular events [69].…”
Section: The Effect Of Treating Anemia On Chfmentioning
confidence: 99%